2021
DOI: 10.31557/apjcp.2021.22.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric-Modulated Arc Radiotherapy with Daily Image-Guidance Carries Better Toxicity Profile for Higher Risk Prostate Cancer

Abstract: Prostate cancer (PCa) is the most common male malignancy and the second cause of cancer death in the United States (US) with expected 248,530 new cases and 34,130 deaths in 2021 (Siegel et al., 2021). Following the 2012 update of the US Preventive Task Force against routine prostate specific antigen (PSA) screening (Moyer, 2012), there has been an increase in the proportion of higher risk localized cases especially in those >75 years at diagnosis (Hu et al., 2016).According to the National Cancer Comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…After further exclusion, 26 articles were eligible for inclusion, but 6 of them were excluded due to the inappropriate form of outcomes [17] , [37] , [38] , [39] , [40] , [41] and 2 were excluded because of the same cohort of patients [42] , [43] . Ultimately, 18 studies that met the eligibility criteria were finally selected, including 3 RCTs, [19] , [23] , [44] 4 PCSs [45] , [46] , [47] , [48] and 11 RCSs [18] , [21] , [22] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] . A PRISMA flow diagram depicting the study identification and selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After further exclusion, 26 articles were eligible for inclusion, but 6 of them were excluded due to the inappropriate form of outcomes [17] , [37] , [38] , [39] , [40] , [41] and 2 were excluded because of the same cohort of patients [42] , [43] . Ultimately, 18 studies that met the eligibility criteria were finally selected, including 3 RCTs, [19] , [23] , [44] 4 PCSs [45] , [46] , [47] , [48] and 11 RCSs [18] , [21] , [22] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] . A PRISMA flow diagram depicting the study identification and selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is known from several studies [ 33 , 34 , 35 , 36 ] that even a small decrease in mean dose and especially relief in the high dose range is associated with a significantly lower rate of proctitis and cystitis, even if these data were not yet clearly reproducible in the patient reported outcome [ 37 ]. The clinical relevance of the present results is thus demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive radiotherapy (RT), a primary intervention for intermediate and high-risk PCa, aims to limit treatment-related side effects and preserve patient quality of life (QOL) while delivering curative dose to the prostate 3 6 . Efforts to minimize toxicity to nearby organs at risk (OAR), mainly gastrointestinal and genitourinary (GU) tissues, have established intensity-modulated radiotherapy (IMRT) as the standard external beam technique for RT of PCa 7 10 . Modern image-guided RT (IGRT) with linac-mounted cone-beam CT (CBCT) improves the therapeutic index through enhanced visualization of the prostate prior to daily treatment, allowing for reduction of planning target volume (PTV) margins and sparing of adjacent OAR 6 , 7 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to minimize toxicity to nearby organs at risk (OAR), mainly gastrointestinal and genitourinary (GU) tissues, have established intensity-modulated radiotherapy (IMRT) as the standard external beam technique for RT of PCa 7 10 . Modern image-guided RT (IGRT) with linac-mounted cone-beam CT (CBCT) improves the therapeutic index through enhanced visualization of the prostate prior to daily treatment, allowing for reduction of planning target volume (PTV) margins and sparing of adjacent OAR 6 , 7 , 11 , 12 . Despite innovations in RT techniques, modalities and fractionation, overall patient QOL suffers compared to men without PCa in part due to RT-related side effects 13 .…”
Section: Introductionmentioning
confidence: 99%